Law Enforcement Against Perpetrators of Online Gambling Crimes by the Cyber Crime Division of the North Sumatra Regional Police Criminal Investigation Unit - Marnaek Tua Benny Purba; Rachmad Abduh (SEAN Institute, 2026)
Discussion results conclude that impact online gambling usually impact on social, economic, psychological and other aspects enforcement law. Even in tracking related cash flows with online gambling that is necessary researched. This approach allows police For browse cash flow​ online gambling so that No only ensnare perpetrator field, but also uncovers the bookies and networks that play a role as controller as well as recipient profit main. With focus on tracking transaction finance, enforcement law become more oriented towards termination cash flow and weakening structure crime in a way comprehensive.